The influence of Pinus radiata, Quercus suber, and improved pasture on soil chemical properties - Noble, A D; Little, I P; Randall, P J (AUSTRALIAN JOURNAL OF SOIL RESEARCH, 1999)
Soil acidification and related land degradation issues are assuming increasing importance in Australia and challenging the concept of sustainability of current land management systems. In this study, the impacts of tree plantations of 2 species and permanent pasture on soil chemical properties are compared. Soil samples were collected from the top 50 cm (0-5, 5-10, 10-15, 15-20, 20-30, and 30-50 cm depths) from 3 adjacent sites carrying pasture and monocultures of Pinus radiata (radiata pine) and Quercus suber (cork oak) on a deep-surfaced yellow podzolic soil, and differences in soil pH and other soil chemical properties were examined. In the surface 0-5 cm, pH was similar at all 3 sites. Below that depth, soil pH was significantly lower and exchangeable Al greater under the cork oak stand than at the other 2 sites. Consistent with a decrease in soil pH there was significantly less exchangeable Ca under cork oak. Also, less clay was observed under the cork oak stand and this is taken as evidence of the degradational impact of soil acidification. An estimate of Ca in the top 50 cm of the soil implies considerable loss of Ca under oak, probably by leaching and loss of litter down the slope. Evidence is presented to show that there has been more Fe and Al movement under oak than under pasture and pine, this being ascribed in part to the greater Al and Fe mobilising capacity of the water-soluble component extracted from freshly fallen leaf litter of oak. The Fe and Al composition of the oxalate extract from concretionary material at 10-30 cm under oak is consistent with a process similar to podzolisation. Pseudogleying of Fe and Al may have accompanied the leaching of bases from the system and a reduction of pH.
Keywords: Acidification; clay cont; exchangeable cations; pH